Analysis of Albania's diplomatic relations with the Soviet Union during the years 1948-1959 [version 2; peer review: 2 approved] - Manjola Xhaferri; mirela tase (F1000Research, 2024)
Background This paper aims to shed light on a very intense period of relations between Albania and the Soviet Union (USSR), focusing on the period from 1948 with the intensification of Albania’s relations with the USSR until the termination of diplomatic relations in 1959. The paper will overview the USSR’s relationship with Albania and its behaviour. Methods The paper analyses a specific period between 1948 and 1959 as a case study. The analysis is conducted on context, actors, and outcomes. The research aims to identify key indicators and the implications of the relationship in both domestic and international contexts. The data sources include various materials such as interviews, films, newspapers, and books. The researchers have requested permission to use the Archival resources of the Albanian Central State Archives (AQSH), where they have made some non-state secret resources accessible. However, some of these resources can only be accessed within the archive, but the researchers have been permitted to use them. Findings The facts show that the relations between Albania and the USSR benefitted Albania more. particularly with economic support from the USSR, which helped Albania emerge from the crisis and build the so-called ‘socialist state.’ Albania took its place in the international arena through these relations and contributions. Conclusions The study, regardless of the issues it addresses, does not aim to exhaust the paper’s topic but to contribute to the objective analysis and to have some impact on the continuation and deepening of the treatment of this topic. Albania’s relations with the Soviet Union are still not fully revealed as long as many documents found in Russian archives are not available for study. But further, numerous documents show that this could be the ‘best cover’ to safeguard the interests and personal power of the leadership.